Pengembangan Aplikasi Lectora Inspire Sebagai Media Pembelajaran terhadap Kemampuan Literasi Sains Siswa Kelas Tinggi - Herda Meidilana; Astri Sutisnawati; Din Azwar Uswatun (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2020)
The research purpose to get advisability of the development of lectora inspire  according to expert faculty, teachers and students and for find out raising of science literacy ability students in high grade with using lectora inspire. Plan of the research using Borg and Gall that has been adaption by Sugiyono. subjects in this research is 3 students five grade of SDN Suryakencana CBM Sukabumi and 6 students five grade of SDN Babakan Caringin Sukabumi. The method of collecting data used are questionnaire and test. The result of the research indicate that development of lectora inspire theme the water cycle suitable for used. The advisability based on validation result of expert faculty and teachers with very good category and students giving good response. Lectora inspire increase students science literacy ability. The raising is can see in gain score students in the first trial products was 0,75 that includes on the high category and in the second trial products was 0,61 that includes on the average category.